2002
DOI: 10.1074/jbc.m201033200
|View full text |Cite
|
Sign up to set email alerts
|

The 3′-Untranslated Region of Chloroplast psbA mRNA Stabilizes Binding of Regulatory Proteins to the Leader of the Message

Abstract: The 5-leader and 3-tail of chloroplast mRNAs have been suggested to play a role in posttranscriptional regulation of expression of the message. The regulation is thought to be mediated, at least in part, by regulatory proteins that are encoded by the nuclear genome and targeted to the chloroplast where they interact with chloroplast mRNAs. Previous studies identified high affinity binding of the 5-untranslated region (UTR) of the chloroplast psbA mRNA by Chlamydomonas reinhardtii proteins. Here we tested wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Genetic evidence from tobacco (Monde et al 2000;Eibl et al 1999) and perhaps Chlamydomonas (Barnes et al 2005) for such interactions can be found with reporter genes whose RNA levels are suggestive of cooperation between certain 5¢ and 3¢ UTRs. Also, protein binding to the 5¢ UTR of psbA is enhanced by the 3¢ UTR (Katz and Danon 2002). The psbA model might be relevant, if the 3¢ UTR of tufA acts by inhibiting binding of stabilizing proteins to the 5¢ UTR.…”
Section: Discussionmentioning
confidence: 96%
“…Genetic evidence from tobacco (Monde et al 2000;Eibl et al 1999) and perhaps Chlamydomonas (Barnes et al 2005) for such interactions can be found with reporter genes whose RNA levels are suggestive of cooperation between certain 5¢ and 3¢ UTRs. Also, protein binding to the 5¢ UTR of psbA is enhanced by the 3¢ UTR (Katz and Danon 2002). The psbA model might be relevant, if the 3¢ UTR of tufA acts by inhibiting binding of stabilizing proteins to the 5¢ UTR.…”
Section: Discussionmentioning
confidence: 96%
“…Most chloroplast mRNAs have an AU-rich 3¢-UTR with a terminal inverted repeat that has been shown to function in mRNA processing and stability, and in promoting translation initiation and polysome association (Hayes et al 1996;Memon et al 1996;Monde et al 2000;Rott et al 1998). Interactions between the 5¢-and 3¢-UTRs have also been shown to impact chloroplast translation (Katz and Danon 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Since the psbA 39UTR may participate in the efficient translation of psbA mRNA (Katz and Danon, 2002), we constructed a 59psbA-petA-39psbA reporter gene. We also constructed a chimeric gene expressing cytochrome f translated under the control of the psbA 59UTR, followed by the first 144 codons of psbA (i.e., up to the 3rd residue of the third transmembrane helix of D1).…”
Section: Assessment Of the Role Of Ces In The Recovery From Photoinhimentioning
confidence: 99%